Effects of fungicide and host resistance on the epidemiology of wheat blast and on plant physiology and changes in the source-sink relationship on wheat during the infection process of Pyricularia oryzae - Rios, Jonas Alberto (2016)
Two field experiments (Exp. 1 and Exp. 2) were carried out to evaluate the spike blast development as well as the physiological performance and grain yield of wheat cultivars BR-18 (partially resistant) and Guamirim (susceptible) inoculated with Pyricularia oryzae and treated or untreated with the fungicide 13.3% epoxiconazole + 5% pyraclostrobin. Relative to Guamirim-untreated, BR-18-untreated (resistance alone) led to 44 and 64% control of final incidence and severity, respectively, in Exp. 1, and 3 and 49% control, respectively, in Exp. 2. Guamirim-treated (fungicide alone) led to 65% control of incidence and 77% control of severity in Exp. 1, and 64% control of incidence and 95% control of severity in Exp. 2. Similarly, there was reduction higher than 75 % in the temporal rate of spike blast progress when host resistance and fungicide were combined. Results from regression analyses indicated that spike and leaf blast severity at 10-14 days after anthesis resulted in greater yield losses (highest negative slope) than severity at 18 to 22 days after anthesis, and that spike blast severity had a greater negative effect on yield than leaf blast severity. Relative to Guamirim-untreated, there was a 0.3 and 16% increase in mean yield for BR-18-untreated (resistance alone), 20 and 61% increase for Guamirim treated (fungicide alone), and 26 and 83% for BR-18 treated (moderate resistance + fungicide) in Exp. 1 and 2, respectively. By virtue of their effects on blast severity, fungicide application and cultivar resistant resulted in higher measures of leaf health (mean HAD, HLAI, HAA and HRI) and photosynthetic performance (based on F v /F m , F m , Y(II), and Y(NPQ)) of both spikes and leaves than the untreated susceptible reference treatment. Results from this study suggesting that the integration of these strategies may be the best approach for managing spike blast and useful for future efforts to develop crop loss models and management guidelines for wheat blast. Additionally, two experiments were carried out in greenhouse conditions to assess the changes associated with photoassimilates production and their partitioning in source-sink relationship on flag leaves and spikes of wheat plants infected with Pyricularia oryzae. Flag leaves and spikes were inoculated at 10 days after anthesis (daa) (Exp. 1) and at 20 daa (Exp. 2) with a conidial suspension of P. oryzae. There was an impairment on chlorophyll a fluorescence parameters (analyzed by F m , F v /F m YII and Y(NO)) on the infected flag leaves and spikes coupled with reduced concentrations of chlorophyll a + b and carotenoids as well as lower capacity of CO 2 fixation by RuBisCO in the infected flag leaves. In these leaves and grains obtained from the infected spikes, there were lower concentration of soluble sugars and an increase on the hexoses to sucrose ratio on the flag leaves. In the infected flag leaves, there was a lower sucrose phosphate synthase (SPS) activity and lower expression of sucrose synthase (Susy) gene coupled with higher expression and activity of acid invertases. These alterations, associated with synthase and degradation of sucrose, suggestss a status sink in the infected flag leaves. At advanced stages of fungal infection, the concentration of starch was reduced on grains whereas on the infected flag leaves its concentration was kept elevated. There were reduction on the activity of ADP-glucose pyrophosphorylase and on the expression of ADP-glucose pyrophosphorylase genes and down regulation of β- and α-amylase expression at late stages of fungal infection on flag leaves and spikes. In conclusion, the greatest effect of blast on both grains quality and yield can be associated with alterations in the production and partitioning of carbohydrates during the grain filling process.